Fusion to Snowdrop Lectin Magnifies the Oral Activity of Insecticidal ω-Hexatoxin-Hv1a Peptide by Enabling Its Delivery to the Central Nervous System - Fitches, Elaine C.; Pyati, Prashant; King, Glenn F.; Gatehouse, John A. (PLOS ONE, 2012)
Background The spider-venom peptide ω-hexatoxin-Hv1a (Hv1a) targets insect voltage-gated calcium channels, acting directly at sites within the central nervous system. It is potently insecticidal when injected into a wide variety of insect pests, but it has limited oral toxicity. We examined the ability of snowdrop lectin (GNA), which is capable of traversing the insect gut epithelium, to act as a “carrier” in order to enhance the oral activity of Hv1a. Methodology/Principal Findings A synthetic Hv1a/GNA fusion protein was produced by recombinant expression in the yeast Pichia pastoris. When injected into Mamestra brassicae larvae, the insecticidal activity of the Hv1a/GNA fusion protein was similar to that of recombinant Hv1a. However, when proteins were delivered orally via droplet feeding assays, Hv1a/GNA, but not Hv1a alone, caused a significant reduction in growth and survival of fifth stadium Mamestra brassicae (cabbage moth) larvae. Feeding second stadium larvae on leaf discs coated with Hv1a/GNA (0.1–0.2% w/v) caused ≥80% larval mortality within 10 days, whereas leaf discs coated with GNA (0.2% w/v) showed no acute effects. Intact Hv1a/GNA fusion protein was delivered to insect haemolymph following ingestion, as shown by Western blotting. Immunoblotting of nerve chords dissected from larvae following injection of GNA or Hv1a/GNA showed high levels of bound proteins. When insects were injected with, or fed on, fluorescently labelled GNA or HV1a/GNA, fluorescence was detected specifically associated with the central nerve chord. Conclusions/Significance In addition to mediating transport of Hv1a across the gut epithelium in lepidopteran larvae, GNA is also capable of delivering Hv1a to sites of action within the insect central nervous system. We propose that fusion to GNA provides a general mechanism for dramatically enhancing the oral activity of insecticidal peptides and proteins.